2007
DOI: 10.1042/bst0351456
|View full text |Cite
|
Sign up to set email alerts
|

HPV: from infection to cancer

Abstract: Infection with HPV (human papillomavirus) 16 is the cause of 50% or more of cervical cancers in women. HPV16 infection, however, is very common in young sexually active women, but the majority mount an effective immune response and clear infection. Approx. 10% of individuals develop a persistent infection, and it is this cohort who are at risk of cancer progression, with the development of high-grade precursor lesions and eventually invasive carcinoma. Effective evasion of innate immune recognition seems to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
176
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 33 publications
1
176
0
10
Order By: Relevance
“…They can promote the transforma-tion of the infected cell by altering the regulation of fundamental cellular events, such as apoptosis and the cell cycle. The E6 and E7 oncoproteins exert their functions by inducing the degradation of two important tumor suppressors, p53 and retino-blastoma (pRb), respectively, and cooperates with each other to immortalize primary keratinocytes (Stanley et al, 2007). However, Hasan UA (Hasan et al, 2007) found that TLR9 expression and function also was abolished by the cervical cancer-associated human papillomavirus type 16.…”
Section: Tlr9 Expression In Uterine Cervical Lesions Of Uyghur Women mentioning
confidence: 99%
“…They can promote the transforma-tion of the infected cell by altering the regulation of fundamental cellular events, such as apoptosis and the cell cycle. The E6 and E7 oncoproteins exert their functions by inducing the degradation of two important tumor suppressors, p53 and retino-blastoma (pRb), respectively, and cooperates with each other to immortalize primary keratinocytes (Stanley et al, 2007). However, Hasan UA (Hasan et al, 2007) found that TLR9 expression and function also was abolished by the cervical cancer-associated human papillomavirus type 16.…”
Section: Tlr9 Expression In Uterine Cervical Lesions Of Uyghur Women mentioning
confidence: 99%
“…In certain primary cells or explant cultures, they have been more difficult to study due to strong innate host anti-virus responses, and the limited availability and batch-to-batch variations of these cells. Nonetheless, there are a number of entry steps that are universally required for infection of diverse cell types with human or prototypic DNA-tumor viruses, including virus attachment to a receptor at the cell surface (for recent reviews, see 34,[35][36][37][38][39][40], and lateral movements of the virus-receptor complex to specialized sites on the plasma membrane (reviewed in 41,42). These lateral movements can lead the virus particles, for example, to tight and adherens junctions, where additional receptors are localized, such as CAR for adenoviruses, or nectins for herpesviruses (34).…”
Section: Dna-tumor Virus Entry Into Cellsmentioning
confidence: 99%
“…4 The HPV genome consists of 3 domains, a non-coding upstream region, an early region containing open reading frames E1, E2, E4, E5, E6 and E7, and a late region encoding the major and minor capsid proteins. 4 In the vast majority of women, infections and HPV-induced lesions are transient and are naturally resolved. However, approximately 10 -20% of women fail to eliminate the virus.…”
mentioning
confidence: 99%
“…However, approximately 10 -20% of women fail to eliminate the virus. 4 In these cases, persistence of infection, viral integration and activation of inflammatory pathways have been linked to neoplastic transformation and malignant progression. 4,5 In this review, we highlight our findings relating to the activation of inflammatory pathways in cervical cancers and address their role in disease progression.…”
mentioning
confidence: 99%